Smaller Hippocampal Volume and Degraded Peripheral Hearing Among Japanese Community Dwellers - Uchida, Yasue; Nishita, Yukiko; Kato, Takashi; Iwata, Kaori; Sugiura, Saiko; Suzuki, Hirokazu; Sone, Michihiko; Tange, Chikako; Otsuka, Rei; Ando, Fujiko; Shimokata, Hiroshi; Nakamura, Akinori (Frontiers in Aging Neuroscience, 2018)
A growing body of literature has demonstrated that dementia and hearing loss are interrelated. Recent interest in dementia research has expanded to brain imaging analyses with auditory function. The aim of this study was to investigate the link between hearing ability, which was assessed using pure-tone audiometry, and the volume of brain regions, specifically the hippocampus, entorhinal cortex, Heschl’s gyrus, and total gray matter, using Freesurfer software and T1-weighted brain magnetic resonance imaging. The data for 2082 samples (age range = 40–89 years) were extracted from a population-based cohort of community dwellers. Hearing-impaired individuals showed significantly smaller hippocampal volumes compared with their non-hearing-impaired counterparts for all auditory frequency ranges. In addition, a correlational analysis showed a significant dose-response relationship for hearing ability and hippocampal volume after adjusting for potential confounding factors so that the more degraded the peripheral hearing was, the smaller the hippocampal volume was. This association was consistent through the auditory frequency range. The volume of the entorhinal cortex, right Heschl’s gyrus and total gray matter did not correlate with hearing level at any frequency. The volume of the left Heschl’s gyrus showed a significant relationship with the hearing levels for some auditory frequencies. The current results suggested that the presence of hearing loss after middle age could be a modifier of hippocampal atrophy.